Two kinds of traditional Chinese medicine prescriptions reduce thymic inflammation levels and improve humoral immunity of finishing pigs - Wang, Xiaoyu; Chen, Jiajia; Yang, Fan; Ali, Farah; Mao, Yaqin; Hu, Aiming; Xu, Tianfang; Yang, Yan; Wang, Feibing; Zhou, Guangbin; Guo, Xiaowang; Cao, Huabin (Frontiers in Veterinary Science, 2022)
In animal husbandry, traditional Chinese medicine (TCM) as a reasonable alternative to antibiotics has attracted more and more concerns to reduce microbial resistance. This study was aimed to investigate the effects of dietary supplementation with TCM prescriptions on serum parameters and thymus inflammation responses in finishing pigs. Thirty finishing pigs were randomly divided into three groups, which included the Con group (basal diet), the TCM1 group (basal diet supplemented with Xiao Jian Zhong prescriptions), and the TCM2 group (basal diet supplemented with Jingsananli-sepsis). The results showed that the contents of C3 and C4 in the serum were significantly increased in both the TCM1 and TCM2 groups compared to the Con group on day 30. Similarly, the levels of IgA, IgG, and IgM were increased in the TCM2 group, and only the level of IgM in TCM1 was increased on day 30. Meanwhile, the levels of classical swine fever virus (CSFV) and respiratory syndrome virus (PRRSV) antibodies had a notable increase in the TCM1 and TCM2 groups. Both TCM1 and TCM2 inhibited the levels of TLR4/MyD88/NF-κB signaling pathway-related mRNA (TLR4, MyD88, NF-κB, IL6, IL8, and TNF-α) and protein (p-IκBα and p-P65) expression levels in the thymus. In conclusion, dietary supplementation with TCM could reduce thymic inflammation levels and improve humoral immunity of finishing pigs.